Serverless design patterns and best practices : build, secure, and deploy enterprise ready serverless applications with AWS to improve developer productivity /: build, secure, and deploy enterprise ready serverless applications with AWS to improve developer productivity. (2018) - Zambrano, Brian
No abstract available